Job Demands, Resources, and Future Considerations: Academics' Experiences of Working From Home During the Coronavirus Disease 2019 (COVID-19) Pandemic - Karatuna, Işıl; Jönsson, Sandra; Muhonen, Tuija (Frontiers in Psychology, 2022)
The coronavirus disease 2019 pandemic has severely affected workers, workplaces, and working practices. In the higher education setting, universities have shifted to distance learning, resulting in profound changes in academics’ work. In this study, we aimed to describe academics’ job demands and resources related to changes in working conditions during the pandemic, and to examine how these changes have affected the perceived occupational well-being of academics. Additionally, we aimed to investigate academics’ expectations and concerns for future academic working practices following the pandemic. The data were collected through semi-structured interviews with 26 academics working at various universities in Sweden. A content analysis was used to identify the key themes from the transcribed interviews. The results indicated that academics experienced a lack of face-to-face communication, absence of an academic environment, work overload, and work-home interference as demanding during the pandemic. In relation to resources, online communication options, appropriate working conditions, organizational-social support, and individual factors were perceived as important. Most respondents perceived negative occupational well-being outcomes. However, academics who had the appropriate resources were less likely to be affected by job demands. Academics’ expectations for future academic work included continuation of working online, flexibility in the choice of workspace, and strengthened digital capacity. Their concerns were related to a lack of face-to-face interaction, management actions and economic implications, and pure digital education. This paper contributes to the literature by illustrating the complexity and diversity of experiences and preferences among academics that are important for universities to consider when organizing and managing future academic work.